Genotypes and population allele frequencies in Atlantic and Pacific herring samples - Pettersson, Mats; Andersson, Leif; Fuentes-Pardo, Angela; Rochus, Christina; Bi, Huijuan; Enbody, Erik; Väniölä, Risto (Uppsala University, 2023)
Individual genotypes, sample IDs and pool-wise allele freqeuncies used in "A long-standing hybrid population between Pacific and Atlantic herring in a subarctic fjord of Norway" (GBE-230119). The data are stored as tab-separated, gzipped textfiles. For the pool frequencies, sample names are in the header. For the individuals, the genotypes for each snp are stored as a single string with out spaces or tabs. The order is the indicated in the sample file, and each individual is represente by two characters (ie haplotype 1 and haplotype 2). Thus, the first and second character represents the first individual, the third and fourth cahncater the second individual et c.
Keywords: Bioinformatics and computational biology not elsewhere classified; Biological adaptation; Evolutionary ecology; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi; Biological Sciences; Biologi; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi)